2021
DOI: 10.1002/admi.202002117
|View full text |Cite
|
Sign up to set email alerts
|

Protein Microarray Immobilization via Epoxide Ring‐Opening by Thiol, Amine, and Azide

Abstract: Lithium chloride LiCl Catalyst Sigma-Aldrich (Germany) Zinc perchlorate Cl 2 O 8 Zn Catalyst Sigma-Aldrich (Germany) Zinc oxide ZnO Catalyst Sigma-Aldrich (Germany) Streptavidin-Cy3 (fluorescent-labeled streptavidin) Streptavidin Conjugation with biotinylated molecules Sigma-Aldrich (Germany) Triphenylphosphine Ph 3 P Catalyst Sigma-Aldrich (Germany) Dimethyl sulfoxide DMSO Solvent Sigma-Aldrich (Germany) Bovine serum albumin BSA Blocker Sigma-Aldrich (Germany) Phosphate buffer saline PBS Buffer Sigma-Aldrich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…
click reactions at the beginning of the 21st century, [1] these reactions are consistently a vital link in the process of biosensing, cell screening, drug delivery, and biofunctionalization. [2][3][4][5][6][7][8] The metal-free click reactions have circumvented the need for toxic catalysts (e.g., Cu I ) and offer a fast reaction rate. [9,10] A successful example is benefitting from the activation by ring strain in the structure of reactants, for example, cycloalkyne or cycloalkane.
…”
mentioning
confidence: 99%
“…
click reactions at the beginning of the 21st century, [1] these reactions are consistently a vital link in the process of biosensing, cell screening, drug delivery, and biofunctionalization. [2][3][4][5][6][7][8] The metal-free click reactions have circumvented the need for toxic catalysts (e.g., Cu I ) and offer a fast reaction rate. [9,10] A successful example is benefitting from the activation by ring strain in the structure of reactants, for example, cycloalkyne or cycloalkane.
…”
mentioning
confidence: 99%
“…For this task, inkjet printing and microchannel cantilever spotting (μCS) were employed. In μCS, inks are spotted in an atomic force microscopy (AFM) by a cantilever with a microchannel connected to an on‐chip reservoir for μL volumes of ink, allowing for chemical reactions in such “micro‐reactors” [4,18,19] . When the cantilever is brought into contact with a surface, ink can transfer by capillary force from the reservoir to the surface.…”
Section: Methodsmentioning
confidence: 99%
“…In μCS, inks are spotted in an atomic force microscopy (AFM) by a cantilever with a microchannel connected to an on-chip reservoir for μL volumes of ink, allowing for chemical in such "micro-reactors". [4,18,19] When the cantilever is brought into contact with a surface, ink can transfer by capillary force from the reservoir to the surface. On porous and moderately hydrophobic substrates, this allows for delivery of sufficient volume of ink for imbibition and bulk functionalization of the substrate interior.…”
mentioning
confidence: 99%
“…In a recent effort, the same group analyzed the optimal click chemistry conditions (functional group, time, temperature and catalyst type) for obtaining high quality biomolecular microarrays by µCS. 111 The spotted biomolecules were functionalized with thiol, amine, or azide groups for evaluating the efficiency of the different click chemistry immobilization onto epoxy treated glass surfaces. By combining optical and XPS analyses, they showed that the most efficient route is based on the amine functionalized biomolecules.…”
Section: Applications In Printed Biochipsmentioning
confidence: 99%